Utilization of genes encoding osmoprotectants in transgenic plants for enhanced abiotic stress tolerance - Khan,Mohammad Sayyar (Pontificia Universidad Católica de Valparaíso, 2015)
Global agriculture in the context of growing and expanding populations is under huge pressure to provide increased food, feed, and fiber. The recent phenomenon of climate change has further added fuel to the fire. It has been practically established now that the global temperature has been on the increase with associated fluctuations in annual rainfall regimes, and the resultant drought and flood events and increasing soil and water salinization. These challenges would be met with the introduction and utilization of new technologies coupled with conventional approaches. In recent years, transgenic technology has been proved very effective in terms of production of improved varieties of crop plants, resistant to biotic stresses. The abiotic stresses such as salt and drought are more complex traits, controlled by many genes. Transgenic plant development for these stresses has utilized many single genes. However, much emphasis has been placed on genes catalyzing the biosynthetic pathways of osmoprotectants. This review focuses on the current status of research on osmoprotectant genes and their role in abiotic stress tolerance in transgenic plants.